What do implicit measures measure?. Issue 5 (29th April 2019) - Brownstein, Michael; Madva, Alex; Gawronski, Bertram
Abstract: We identify several ongoing debates related to implicit measures, surveying prominent views and considerations in each. First, we summarize the debate regarding whether performance on implicit measures is explained by conscious or unconscious representations. Second, we discuss the cognitive structure of the operative constructs: are they associatively or propositionally structured? Third, we review debates about whether performance on implicit measures reflects traits or states. Fourth, we discuss the question of whether a person's performance on an implicit measure reflects characteristics of the person who is taking the test or characteristics of the situation in which the person is taking the test. Finally, we survey the debate about the relationship between implicit measures and (other kinds of) behavior. This article is categorized under: Philosophy > Representation Psychology > Theory and Methods Psychology > Prediction Philosophy > Psychological Capacities Abstract : This article summarizes five ongoing debates regarding the status of implicit measures.